Whatever happened to China's neglected tropical diseases? - Peter J. Hotez (BMC, 2019)
Abstract Before the founding of the People's Republic of China 70 years ago, both extreme poverty and parasitic infections and other neglected tropical diseases were highly prevalent. Owing to social development, particularly economic reforms since the 1980s, poverty has since been dramatically reduced, and China became increasingly urbanized and industrialized. In parallel, China's economic transformation translated into similar and remarkable reductions in neglected tropical diseases. Qian and colleagues report in their review published in Infectious Diseases of Poverty, the elimination or near elimination as a public health problem of lymphatic filariasis, trachoma, soil-transmitted helminth infections, schistosomiasis and other neglected tropical diseases. Of note, neglected tropical disease control and poverty reduction each appear to reinforce the other. China's formula for success in parasitic and neglected tropical disease control might translate to other parts of the world, such as in sub-Saharan Africa through China's new Belt and Road Initiative.